Development of A Chemistry E-Module Based on Project Based Learning Using the Flipbook Application to Improve Learning Outcomes and Train Collaboration on Acid Base Material - Hany, Nadila Cempaka; Syafriani, Dewi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This research aims to: (1) determine the validity of PjBL-based e-modules, (2) determine the practicality of PjBL-based e-modules, (3) determine the effectiveness of PjBL-based e-modules, and (4) determine whether there is a significant correlation between collaboration and learning outcomes. This research was conducted at SMA Negeri 1 Stabat with the sample studied being class Data analysis techniques were carried out by: e-module feasibility test according to BSNP, collaboration skills test, and correlation test between collaboration skills and learning outcomes. The results obtained in this research are: (1) The PjBL-based E-module is said to be "valid" after being validated by 1 chemistry lecturer with an average material assessment of 89% and an average media assessment of 95% which can be categorized as " very worthy”; (2) PjBL-based e-modules are said to be "practical" after receiving chemistry teacher responses with an average percentage of 97% which can be categorized as "very feasible" and student responses with an average rating of 87%; (3) The PjBL-based e-module is said to be "effective" with a posttest score of 82.17 which has increased from 47.33. So the N-Gain score was obtained at 0.66 (65.72%) which is in the medium criteria; (4) There is a positive and significant correlation between collaboration skills and student learning outcomes where rcount is 0.593 and rtable is 0.361.